Atorvastatin Effectively Inhibits Ancestral and Two Emerging Variants of SARS-CoV-2 in vitro (2022)
ABSTRACT: This article evaluated the in vitro antiviral effect of atorvastatin (ATV) against SARS-CoV-2 and identified the interaction affinity between this compound and two SARS-CoV-2 proteins. The antiviral activity of atorvastatin against this virus was evaluated by three different treatment strategies [(i) pre-post treatment, (ii) pre-infection treatment, and (iii) post-infection treatment] using Vero E6 and Caco-2 cells. The interaction of atorvastatin with RdRp (RNA-dependent RNA polymerase) and 3CL protease (3-chymotrypsin-like protease) was evaluated by molecular docking. The CC50s (half-maximal cytotoxic concentrations) obtained for ATV were 50.3 and 64.5 μM in Vero E6 and Caco-2, respectively. This compound showed antiviral activity against SARS-CoV-2 D614G strain in Vero E6 with median effective concentrations (EC50s) of 15.4, 12.1, and 11.1μM by pre-post, pre-infection, and post-infection treatments, respectively. ATV also inhibited Delta and Mu variants by pre-post treatment (EC50s of 16.8 and 21.1μM, respectively). In addition, ATV showed an antiviral effect against the D614G strain independent of the cell line (EC50 of 7.4μM in Caco-2). The interaction of atorvastatin with SARS-CoV-2 RdRp and 3CL protease yielded a binding affinity of −6.7kcal/mol and −7.5kcal/mol, respectively. Our study demonstrated the in vitro antiviral activity of atorvastatin against the ancestral SARS-CoV-2 D614G strain and two emerging variants (Delta and Mu), with an independent effect of the cell line. A favorable binding affinity between ATV and viral proteins by bioinformatics methods was found. Due to the extensive clinical experience of atorvastatin use, it could prove valuable in the treatment of COVID-19.